2019
DOI: 10.3389/fimmu.2019.00255
|View full text |Cite
|
Sign up to set email alerts
|

Paralogs of Common Carp Granulocyte Colony-Stimulating Factor (G-CSF) Have Different Functions Regarding Development, Trafficking and Activation of Neutrophils

Abstract: Mammalian granulocyte colony-stimulating factor (G-CSF; CSF3) is a primary cytokine that promotes the development, mobilization, and activation of neutrophils and their precursors. Teleosts have been reported to possess two paralogs as a likely result of the teleost-wide whole genome duplication (WGD) event, but functional divergence of G-CSF paralogs remains poorly understood. Common carp are an allotetraploid species owing to an additional WGD event in the carp lineage and here, we report on genomic synteny,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 74 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…The response of the neutrophil/heterophil-to-lymphocyte ratio to long-term environmental stressors is detectable over relatively long periods of time, in contrast to the temporary increase in hormone levels ( 130 ). Infections also have a decisive influence on the proliferation and trafficking of leukocytes ( 131 ), and the coincidence of stress and immune responses can have an antagonistic effect on the ultimate number of peripheral leukocytes ( 132 ).…”
Section: Hematological Profiling and Blood Cell Sortingmentioning
confidence: 99%
“…The response of the neutrophil/heterophil-to-lymphocyte ratio to long-term environmental stressors is detectable over relatively long periods of time, in contrast to the temporary increase in hormone levels ( 130 ). Infections also have a decisive influence on the proliferation and trafficking of leukocytes ( 131 ), and the coincidence of stress and immune responses can have an antagonistic effect on the ultimate number of peripheral leukocytes ( 132 ).…”
Section: Hematological Profiling and Blood Cell Sortingmentioning
confidence: 99%
“…observed DNA hypomethylation in a human macrophage cell line upon exposure to Burkholderia pseudomallei consistent with our results, the work of Marr et al . demonstrates DNA hypermethylation events associated with Leishmania donovani infection of THP-1 macrophages [ 21 , 34 , 35–39 ]. Additional infection models and testing of alternate disease-related pathogens or pathogen-derived secreted products are required to better understand DNA alterations in host-pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…A study looking at neutrophils in systemic inflammation response syndrome (SIRS) in a murine model found that mild SIRS induced a pro-inflammatory phenotype (IL-12+CCL3+) while severe SIRS induced an anti-inflammatory phenotype (IL-10+CCL2+) ( 6 , 14 ). G-CSF production (monocytes, macrophages, fibroblasts, endothelial cells, and bone marrow stromal cells) is regulated by IL-17A which is produced by T cells, natural killer (NK) cells, and macrophages ( 6 , 11 , 15 ). Neutrophils produce CCL2 and CCL20 which are critical for recruitment of T helper cells, a major producer of IL-17A ( 10 , 16 ).…”
Section: Macrophage Dysregulation In Viral Pathogenesismentioning
confidence: 99%